Temperature and impurity concentration effects on upconversion luminescence in LaInO3 doped with Er3+ - Sarakovskis, A.; Grube, J.; Strals, K.; Krieke, G.; Springis, M.; Mironova-Ulmane, N.; Skvortsova, V.; Yukhno, E.K.; Bashkirov, L.A. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2016)
In this paper a novel method for synthesis of LaInO3 : Er3+ is reported and upconversion luminescence properties of the synthesized material at different temperatures (9–300 K) are studied. The samples were prepared by co-precipitation and subsequent heat treatment of lanthanum, indium and erbium hydroxides. It is shown that the excitation at 980 nm leads to a strong green upconversion luminescence in the material. At the concentrations above 0.1 mol % of Er3+ the energy transfer upconversion mechanism of the luminescence becomes evident.Further increase of Er3+ content in the material leads to higher red-to-green upconversion luminescence intensityratio. The mechanisms responsible for the observed variation are discussed.